Exploratory Study on the Application of Starter and Inoculum of Trichoderma sp. with Various Dosages on the Reduction of Moisture Content in Cattle Manure Composting - Gustin Meynindra Sasa Dilla; Agus Purwanto (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Cattle manure is an organic waste with high moisture content that can slow down decomposition and produce unpleasant odors. Improving composting efficiency can be achieved by adding Trichoderma sp. as a bioactivator. This fungus produces cellulolytic enzymes that accelerate the breakdown of organic matter while promoting water evaporation. This study explored the application of starter incubated on cattle manure substrate and commercial inoculum applied directly, each with three dosage variations (42 g, 38 g, and 10 g) per reactor. The observed parameters included moisture content, pH, and temperature on days 0, 8, and 14 to evaluate the dynamics of the decomposition process. The results are expected to provide preliminary information on the effectiveness of Trichoderma sp. in reducing the moisture content of cattle manure and to serve as a basis for the development of organic waste management technologies through bioconversion.